2019
DOI: 10.1007/s11071-019-04818-9
|View full text |Cite
|
Sign up to set email alerts
|

On the properties of a class of higher-order Mathieu equations originating from a parametric quantum oscillator

Abstract: Evolution in time of an arbitrary initial state for a parametrically driven quantum oscillator is an interesting problem since there exist regions in parameter space (defined by the amplitude and frequency of the driving) where the moments of the probability distribution can diverge in time. While the first moment satisfies a Mathieu equation, the higher-order moments follow Mathieu like equations of order greater than two. It is not very often that a physical problem gives rise to higher-order Mathieu equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…On the one hand, a large makes spar buoys unresponsive in roll/pitch, hence ideal for both classic offshore applications and wave energy converters operating in heave. On the other hand, since is so large, typically falls in the range of operational wave periods, generating conditions for roll/pitch parametric resonance to settle [ 4 ]. Several experimental studies have confirmed the appearance of parametric roll in container ships [ 35 ], spar platforms [ 29 ] and wave energy converters (WECs), either spar buoys [ 7 , 23 ] or self-reacting [ 5 , 30 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, a large makes spar buoys unresponsive in roll/pitch, hence ideal for both classic offshore applications and wave energy converters operating in heave. On the other hand, since is so large, typically falls in the range of operational wave periods, generating conditions for roll/pitch parametric resonance to settle [ 4 ]. Several experimental studies have confirmed the appearance of parametric roll in container ships [ 35 ], spar platforms [ 29 ] and wave energy converters (WECs), either spar buoys [ 7 , 23 ] or self-reacting [ 5 , 30 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of the variance as shown in Eq. (2.13) has been investigated in [4]- [5] for µ = 0 (periodic modulation). We note that from Eqs.…”
Section: The Equation Of Motionmentioning
confidence: 99%
“…It is around the periodic responses that the instability zones exist. It was shown in Ref [5] from harmonic balance arguments that there is no instability zone around T = 3π ω and so in Sec III we discuss the case around T = 2π ω , i.e. twice the natural frequency.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Most investigations in literature deal with the corresponding stability transition curves [3]. Some works analyze the stability of two coupled Mathieu equations [4][5][6]. In general, an asymptotic or a numerical analysis method is required for analyzing this class of systems.…”
Section: Introductionmentioning
confidence: 99%